A dual purpose universal influenza vaccine candidate confers protective immunity against anthrax. Issue 3 (5th December 2016) - Arévalo, Maria T.; Li, Junwei; Diaz‐Arévalo, Diana; Chen, Yanping; Navarro, Ashley; Wu, Lihong; Yan, Yongyong; Zeng, Mingtao
Summary: Preventive influenza vaccines must be reformulated annually because of antigen shift and drift of circulating influenza viral strains. However, seasonal vaccines do not always match the circulating strains, and there is the ever‐present threat that avian influenza viruses may adapt to humans. Hence, a universal influenza vaccine is needed to provide protective immunity against a broad range of influenza viruses. We designed an influenza antigen consisting of three tandem M2e repeats plus HA2, in combination with a detoxified anthrax oedema toxin delivery system (EFn plus PA) to enhance immune responses. The EFn‐3×M2e‐HA2 plus PA vaccine formulation elicited robust, antigen‐specific, IgG responses; and was protective against heterologous influenza viral challenge when intranasally delivered to mice three times. Moreover, use of the detoxified anthrax toxin system as an adjuvant had the additional benefit of generating protective immunity against anthrax. Hence, this novel vaccine strategy could potentially address two major emerging public health and biodefence threats. Abstract : A new influenza antigen consisting of three tandem M2e repeats plus HA2, in combination with a detoxified anthrax oedema toxin delivery system (EFn plus PA) was created as a mucosal vaccine. When intranasally delivered to mice, the vaccine generated protective immunity against both influenza and anthrax. This novel vaccine strategy could potentially address two major emerging public health and biodefence threats.